2018
DOI: 10.1590/1806-90882018000400005
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Attributes in Response to Tree Distance and Sun-Exposed Faces After the Implantation of an Integrated Crop-Livestock-Forestry System

Abstract: The use of trees in integrated crop-livestock-forestry systems (ICLF) allows diversifying production, increasing profitability per area, and providing a higher animal comfort. However, the influence of tree component on soil chemical attributes in this system is still little studied. This study aimed to assess the effect of trees and sun-exposed faces to solar radiation on soil nutrient availability at different distances of tree rows in an integrated crop-livestock-forestry system. This study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…According to Moreira et al (2018), the forest component within the system could affect the availability of nutrients for the other crops. This availability varies according to the distance from the tree, and significant changes in soil properties occur nearer the trees, due to greater litter deposition and lower exposure to solar radiation, factors that influence litter decomposition.…”
Section: Soil Toc and Cmic Within The Silvopastoral Systemmentioning
confidence: 99%
“…According to Moreira et al (2018), the forest component within the system could affect the availability of nutrients for the other crops. This availability varies according to the distance from the tree, and significant changes in soil properties occur nearer the trees, due to greater litter deposition and lower exposure to solar radiation, factors that influence litter decomposition.…”
Section: Soil Toc and Cmic Within The Silvopastoral Systemmentioning
confidence: 99%
“…These agroforestry systems has received the attention of farmers and researchers due to its greater versatility in the use and productivity of the areas, considering all the components involved (Moreira et al 2018). The ICLF system also provides improvements in the chemical, physical and biological properties of the soil, prevents erosion, promotes carbon sequestration, the conservation of water resources and biodiversity, in addition to several technical, economic and social bene ts (Serra et al 2012;Almeida et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These initiatives are in compliance with up to date exploration strategies, such as the concept of ecosystem services . Besides, some studies in Brazil have already showed positive effects of adoption of more intensive and diversified pasture management systems over C sequestration Ghahramania and Bowranb, 2018), as well as over soil chemical (e.g., N, P and K) Moreira et al, 2018) and biochemical (e.g., soil enzyme activities, C an N stored in the microbial biomass) (Acosta-Martínez et al, 2010; properties. Nevertheless, knowledge about the relationships between chemical and biochemical properties with soil microorganisms under more intensive and diversified pasture management systems remains unclear, especially in the different edaphoclimatic conditions of Brazil (Melillo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%